THE FOUR STAGES OF PREVENTING QUALITY DEFECTS IN PRODUCT MANUFACTURING - Ibroximjon Khasanov (European Science Publishing, 2023)
After the mass production of the product, the elimination of quality defects often causes a delay in the delivery time to the customer. In this regard, a study was conducte on mass production enterprises, and their advantages and disadvantages were determined during the study. Considering all possible options for eliminating quality defects, optimal ways of development were determined. Based on the received information, the relevance of the selected project topic was justified. The causes of quality defects in product production were finding, and four stages of preventing quality defects were show to these causal factors.
Keywords: Production, quality defects, raw materials, causes of quality defects, four steps to prevent quality defects, determination of quality indicators, tolerance, defective and non-defect.